Which Fish? Knowledge, Articulation, and Legitimization in Claims about Endangered and Culturally Significant Animals. (May 2017) - Buchanan, Nicholas
This article examines how the authorization of scientific discourses in the US Endangered Species Act (ESA) of 1973 has influenced the ways people make claims about culturally significant animals. In it, I focus on struggles over the management of two endangered fish species among a federally recognized Native American tribe, state resource managers, and other actors. I discuss how the requirements of the ESA, namely that decisions regarding the protection of endangered species must be made based "solely on the basis of the best scientific…data available, " have pushed people to reframe their cultural claims about the environment as scientific claims in order to gain legal authority. I argue that these animals span the social worlds of indigenous hunters and fishers, regulators, and ecological scientists. As such, they offer the opportunity to interrogate the relationships among ways of knowing the environment. I suggest that strict divisions among "types" of knowledge as well as hard-and-fast bonds between groups and "their" knowledge become problematic. Instead, people assemble eclectic articulations of knowledge to make the most authoritative claim possible in a given context, contradicting the assumption that certain people know the world only, or primarily, in a particular way.